Mégalithes de haute Bretagne Les monuments de la forêt de Brocéliande et du Ploërmelais : structures' mobilier et environnement - Briard, Jacques (Documents d'archéologie française, 1989)
The abundance of megaliths on the cost of Brittany has hidden for a long time the existence of megaliths inside the peninsula This work summarizes four years on the field (1982-1985) and brings new informations about this type of architecture, ignored until now, through three monuments from the Neolithic and the Bronze Age. Laboratory studies add to classical field data informations allowing to replace the megaliths in their environment and to demonstrate the existence of an economic system based upon exchange, ending the myth of autarky inside "the large forest". This work also analyses modem acculturations of these monuments settled in an area where celtic and arthurian legend is still very much alive.